A 3D Printing Scaffold Using Alginate/Hydroxyapatite for Application in Bone Regeneration - Alves, Bruno C. [UNESP]; de Miranda, Renato S. [UNESP]; Frigieri, Barbara M. [UNESP]; Zuccari, Debora A.P.C.; de Moura, Marcia R. [UNESP]; Aouada, Fauze A. [UNESP]; Tokimatsu, Ruís C. [UNESP] (FapUNIFESP (SciELO), 2023)
This work aimed to manufacture scaffolds from a hydrogel composed of a sodium alginate matrix with hydroxyapatite reinforcements using a 3D bioprinter, aiming at application in bone tissue regeneration. The alginate solution was prepared by dissolving sodium alginate at a concentration of 10% (w/v). Hydroxyapatite (HAp) was added to the solution at 2.5% and 5.0% (w/v) concentrations, followed by placing the samples in a container with a 1.0% (w/v) calcium chloride solution. The scaffolds were analyzed for HAp concentration and morphological characteristics, physicochemical properties, and biological response. The scaffolds show reproducibility and spectroscopic analyses confirm hydrogel formation and hydroxyapatite incorporation in the alginate matrix. The hydrophilic properties are compatible with scaffolds obtained through 3D printing made from polysaccharides, and the thermal analysis showed the expected behavior of these same materials. Preliminary findings indicated that scaffolds containing 2.5% (w/v) hydroxyapatite are inside cytotoxicity limit (66.4 ± 7.0%) towards canine E20 lineage cells. In contrast, scaffolds with 0% and 5.0% (w/v) hydroxyapatite were non-cytotoxic. Notably, the latter scaffold demonstrated enhanced cell proliferation, as anticipated, owing to the hydrophilic properties of alginate that enable easy and swift cell seeding, facilitating nutrient transport and cellular growth within the scaffold.
Keywords: alginate; biomaterials; Hydrogel; hydroxyapatite; scaffolds